Scanning in Dentistry: A Systematic Review - Antarik Dhar (Journal of Pharmacy and Bioallied Sciences)
With a focus on optical impressions, this literature review examines the development, present state, and potential future effects of scanning technology in dentistry. From confocal laser scanning to accordion fringeinterferometry (AFI), we explore the imaging principles of various dental scanners, such as iTero Element, TRIOS 3, Lava C.O.S., True Definition, and CEREC Omnicam. The manual and electronic literatures of previous ten years in the databanks of the PubMed, Web of Science, and Scopus were conducted. The search terms were “intraoral scanner” AND “diagnosis*” OR “Dental Scanners.” The types of studies included were restricted to the original studies and human trials. Analyses of subgroups and meta-regression were used to calculate the heterogeneity. Twenty-eight papers were considered in the review and the results cover primary conclusions, oral diseases identified by intraoral scanning (IOS), and oral diagnostic tools. This review enhances our understanding of IOS scanning in dentistry by exploring its diagnostic effectiveness across various oral disorders. The review explores scanning technology in dentistry, highlighting its revolutionary effects and future applications. It is a valuable resource for professionals and academics in this field amid its digital transformation.